[Portuguese original] Coaches’ knowledge sources: a case study of brazilian men's handball teams - Mendes, José Carlos (2020)
The aim of the current study is to identify the knowledge sources most valued by coaches and assistant coaches of male Brazilian handball teams in the youth (U19), junior (U21), and adult categories. The case study included three coaches and three assistant coaches of male Brazilian handball teams. Data was collected using the Coach Training Profile Questionnaire and analyzed using descriptive (median) and inferential statistics (Mann-Whitney U and Kruskal-Wallis tests), at p ≤ .05 significance level.  Results indicated that coaches and assistant coaches of the national handball teams give greater value to knowledge sources under “professional experience” and “academic training”. In addition, “professional experience” was the knowledge source most valued by members of the technical commission of the U19 and adult categories, whereas members of the technical committee of the U21 category most valued “academic training” as their knowledge source. However, no significant differences were observed in results between coaches and assistant coaches, as well as between the technical commissions of the U19, U21, and adult categories. The professional performance of coaches and assistant coaches of Brazilian male handball teams belonging to the U19, U21, and adult categories and the construction of the training process associated with the match model proposed for the teams are structured based on knowledge sources such as “professional experience” and “academic training”.